Analysis of postmarketing neuropsychiatric adverse events of avapritinib based on the FDA adverse event reporting system - Wei Mao; Junyan Jiang; Yanping Xia; Lin Zhang (Scientific Reports)
Abstract Neuropsychiatric adverse events (AEs) significantly impact the quality of life of patients using avapritinib. However, the majority of current data comes from pre-marketing, with limited real-world studies. Our research aimed to explore post-marketing data of avapritinib. We evaluated the signals of avapritinib-related neuropsychiatric AEs by data mining using the FDA Adverse Event Reporting System (FAERS). Reporting odds ratio (ROR) and information component (IC) were employed to quantify the signals from the first quarter of 2020 through the fourth quarter of 2023. Subsequently, stratified analyses were conducted to further explore the effect of different stratification schemes on the association between avapritinib and neuropsychiatric AEs. Finally, a combination medication analysis was conducted to explore the impact of the co-administration of neuropsychiatric AEs. A total of 2029 neuropsychiatric AEs were reported, and 49 signals were detected, of which 5 were determined to be new signals. Avapritinib was significantly associated with the occurrence of neuropsychiatric AEs (ROR: 1.52, 95% CI: 1.44–1.61; IC: 0.43, IC025: 0.35). The stratified analysis found that gender, age and eight preferred terms (PTs), including cerebral haemorrhage, may affect the severity of AEs. Combination medication analysis showed that combining avapritinib with 19 other medications, including prochlorperazine, may increase the risk of neuropsychiatric AEs. The median time-to-onset (TTO) of avapritinib-related neuropsychiatric AEs was 32 (interquartile range [IQR] 2-200) days, with about 65% of cases occurring within the first three months of treatment. An increase in the signal for neuropsychiatric AEs was identified in post-marketing studies of avapritinib. Clinicians are advised to remain vigilant for such events, particularly during the initial stages of treatment with avapritinib.